PENERAPAN PRINSIP ANDRAGOGI DALAM PROSES PEMBELAJARAN PROGRAM KESETARAAN PAKET C DI PKBM INSAN CENDEKIA KOTA PEKANBARU - Sagala, Nia Sabrina; Wilson, Wilson; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formulation of the problem in this study is how the principle of andragogy can be applied in the learning process of the package C equality program on PKBM Insan Cendekia Kota Pekanbaru. In accordance with the problem formulation, the aim of this study was to find out how to apply the andragogy principle in the learning process of the package C equality program at PKBM Insan Cendekia Kota Pekanbaru.This study uses descriptive research with a qualitative approach that aims to provide a systematic picture of the application of the principle of andragogy in the learning process in the package C equality program of PKBM Insan Cendekia Kota Pekanbaru. Informants in this study were 4 informants consisting of 2 key informants, 1 control informant and 1 observer informant. The application of the principle of andragogy in the learning process can generally be done well by teachers. This can be deduced from the implementation of learning by teachers who pay attention to the principles of andragogy, such as the law of learning, setting goals, developing attitudes, ideals and interests, informing citizens of learning to learn, discussing issues, and habits of citizens who learn in education and are seen from the activities of citizens. learn in the learning process. But when developing psychomotor skills, the learning population of tutors is less total in its application. Informants in this study were 4 informants consisting of 2 key informants, 1 control informant and 1 observer informant.Key Words: Andragogy, Learning Process, Package C Program